Effect of Addition of Purified Diglycerol Linoleic Acid Esters on the Crystallization Behavior of Diacylglycerol Oils. (10th September 2016) - Wan, Fenlong; Teng, Yinglai; Zou, Long; Yang, Xue; Chen, Qiong; Li, Aijun; Wang, Yong
Abstract: Liquid oils containing high‐melting diacylglycerols (DAGs) are more likely to cause precipitation than triacylglycerol‐based oils during long‐term storage, which is not desired for consumer products. Therefore, we attempted to retard the crystallization of high‐melting DAGs by adding emulsifiers, diglycerol esters of fatty acids (DGEs), which were synthesized by esterification of diglycerol and linoleic acid using Novozym 435. The reaction product was isolated by silica gel column chromatography to obtain pure mono‐, di‐, and triesters of diglycerol, and the composition was analyzed by HPLC and ESI‐MS. Further structural analysis of the purified products was performed by 1 H‐ and 13 C‐NMR. The retardation effect of DGEs with a different esterification degree on the crystallization of DAGs was investigated using solid fat content, differential scanning calorimetry, polarized light microscopy, and X‐ray diffraction. The results reveal that addition of 0.5 % (w/w) DGEs could effectively retard the crystallization of high‐melting DAGs by inhibiting the nucleation process and delaying the crystal growth, but their addition did not alter the crystal forms of DAGs. Moreover, the retardation effect was enhanced as the esterification degree of DGE decreased.